Hadis ilminde telfîk yöntemi ve Sahîh-i Buhârî’de telfîkli rivayetler - Civelek, Öznur (My University, 2023)
Sözlükte “birleştirmek” anlamına gelen telfîk, hadis ilminde iki veya daha fazla isnâdın tek siyakla nakledilmesini ifade eder. Cem‘u’l-esânîd ve el-cem‘u beyne’ş-şuyûh terimleriyle de açıklanan telfîk uygulaması, idrâc ve tahvilden ayrı bir yöntem olup hadis rivayetinde ve tarihi haberlerde farklı şekillerde uygulanmıştır. Tarihi bir vakıaya dair farklı rivayetlerin birleştirilip müteselsil biçimde anlatıldığı telfîkli rivayetler, tarih yazıcılığının nüvesini oluştururken telfîk yöntemi, muhaddisler tarafından pek hoş karşılanmamış görünmektedir. Ancak muhaddislerin teorik zeminde telfike karşı olumsuz yaklaşımına rağmen birçok hadis râvisinin telfîke başvurması, hatta çoğu musannifin telfîkli rivayetleri eserine alması hadisçiler nezdinde telfik yönteminin araştırılmasını önemli hale getirmektedir. Bu çalışmada da hem telfîk yönteminin mahiyeti ele alınmış hem de muhaddislerin telfîkli rivayetler konusundaki yaklaşımını ortaya koyabilmek için sıhhat iltizam etmede en titiz musannif olduğu müsellem olan Buhârî’nin el-Câmiu’s-sahih’te yer verdiği telfîkli rivayetlerin tetkiki hedeflenmiştir. Bu amaçla Sahîh-i Buhârî’de yer alan telfîkli rivayetler tasnif edilerek en sık kullanılan telfîk terkipleri, metinleriyle birlikte tahlil edilmiştir. el-Câmiu’s-sahîh’teki rivayetler üzerinden okunan telfîk pratiği, mahiyeti, sınırları ve uygulanış şekilleri açısından telfîkin teorik çerçevesini de açığa çıkarmıştır. Bu tetkik neticesinde telfîkin, birleştiren ve birleştirilen râviler arasında doğrudan irtibatı gerekli kılan cem usûllerinden biri olduğu, râvilerin telfîk yapmadaki amaçları ve lafızlar konusundaki titizliğine göre rivayet döneminde farklı şekillerde uygulandığı, telfîk yapan râviler ve uygulayış şekillerine göre kabul ya da reddedilen bir yöntem olduğu anlaşılmıştır.

The word “talfiq”, which means to combine, refers to the transmission of two or more isnads with a single text in hadith. Talfîq application, which is also explained with the terms “Cam‘u al-asânîd” and “al-cam‘u bayna ash-shuyûh”, is a different method from idrac and tahvil, it has been applied in different ways in hadith narration and historical news. While the transmissions with talfiq in which different narrations about a historical event are combined and explained in succession is forming the core of historiography, the talfîq method seems not to have been welcomed by the hadith scholars. However, despite the negative approach of the hadith scholars towards talfiq on the theoretical ground, the fact that many hadith narrators applied to talfiq, and even that most of the authors transmitted the narrations with talfiq in their works, makes it important to research the talfiq method in the eyes of hadith scholars. In this study, it is aimed to examine both the nature of the talfîq method and the narrations, that are included in al-Cami as-sahih by Bukhari, who is the most meticulous scholar, in order to reveal the approach of the muhaddithun about the narrations with talfiq. For this purpose, the narrations with talfiq in Sahih-i Bukhari were classified and the talfiq combinations, which is most frequently used in it, were analyzed together with their texts. The practice of talfîq, which is read through the narrations in al-Cami as-sahih, has also revealed the theoretical framework of talfiq in terms of its nature, limits and application forms. As a result of this examination, it has been understood that talfiq is one of the methods of cam and necessitating direct contact between the narrator who combine and the narrators who are combined, that it was applied in different ways in the narration period according to the aims of the narrators while applying talfiq and their meticulousness on the words of hadith, and that it is a method that is accepted or rejected according to the narrators who applied to talfiq and the way of application.
Keywords: cem‘u’l-esânîd; Hadis; Hadith; hadith of Ifk; idrac; idrâc; İfk hadisi Talfiq; Sahih al-Bukhari; Sahîh-i Buhârî; Telfîk